2014
DOI: 10.1097/tgr.0000000000000001
|View full text |Cite
|
Sign up to set email alerts
|

Communication Difficulty and Relevant Interventions in Mild Cognitive Impairment

Abstract: Mild Cognitive Impairment (MCI) represents a critical point for controlling cognitive decline. Patterns of communication difficulty have been observed in patients with MCI and warrant examination and management. The present systematic review examined (1) characteristics of communication difficulty in MCI by focusing on two domains: expressive and receptive communication, and (2) cognitive interventions that addressed communication difficulties in individuals with MCI. Of the 28 observational studies we reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 66 publications
(120 reference statements)
1
16
0
5
Order By: Relevance
“…38 , 39 In the scientific literature, the communication complaints of elderly people with MCI are rarely explicit and are frequently associated with memory impairment, such as difficulties in naming and remembering words. 9 The compensatory communicative capacities are evidenced when applying a questionnaire on communication, and the result demonstrates the need for independence in daily life communication. 14…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…38 , 39 In the scientific literature, the communication complaints of elderly people with MCI are rarely explicit and are frequently associated with memory impairment, such as difficulties in naming and remembering words. 9 The compensatory communicative capacities are evidenced when applying a questionnaire on communication, and the result demonstrates the need for independence in daily life communication. 14…”
Section: Discussionmentioning
confidence: 94%
“…The results showed that there were no significant differences between the groups for naming, although an association was found with an increase in age. 40 On the other hand, naming difficulties have been reported in the elderly with MCI, 9 as well as problems with different components of semantic cognition, especially memory. 41 These changes are due to failure in the executive process of semantic activation control; as the disease develops, semantic knowledge also begins to degrade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ao considerar que a dependência de comunicação é um importante indicador da capacidade cognitiva do idoso 14 , que sua identificação precoce é indispensável na prevenção de incapacidades funcionais nessa faixa etária 3 e que há uma escassez de estudos com essa temática, os objetivos dessa pesquisa foram descrever a média total de independência geral e por domínios de comunicação dos idosos da comunidade e verificar as variáveis sociodemográficas e de saúde associadas à maior média de independência de comunicação entre os idosos.…”
unclassified